Prenatal Alcohol Exposure Is Associated with Altered Subcellular Distribution of Glucocorticoid and Mineralocorticoid Receptors in the Adolescent Mouse Hippocampal Formation - Caldwell, Kevin K (BlackWell Publishing Ltd, 2014)
BACKGROUND: Accumulating evidence indicates that several of the long-term consequences of prenatal alcohol exposure (PAE) are the result of changes in the development and function of cortico-limbic structures, including the hippocampal formation. The glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) are key regulators of hippocampal formation development, structure, and functioning and, thus, are potential mediators of PAE’s effects on this brain region. In the present studies, we assessed the impact of PAE on components of corticosteroid signaling pathways in the mouse hippocampal formation. METHODS: Throughout pregnancy, mouse dams were offered either 10% (w/v) ethanol sweetened with 0.066% (w/v) saccharin (SAC) or 0.066% (w/v) SAC alone using a limited (4-hour) access, drinking-in-the-dark paradigm. The hippocampal formation was isolated from naïve postnatal day 40 to 50 offspring, and subcellular fractions were prepared. Using immunoblotting techniques, we measured the levels of GR, MR, 11-β-hydroxysteroid dehydrogenase 1 (11β-HSD1), and the FK506-binding proteins 51 (FKBP51, FKBP5) and 52 (FKBP52, FKBP4). Finally, we determined the effect of PAE on context discrimination, a hippocampal-dependent learning/memory task. RESULTS: PAE was associated with reduced MR and elevated GR nuclear localization in the hippocampal formation, whereas cytosolic levels of both receptors were not significantly altered. FKBP51 levels were reduced, while FKBP52 levels were unaltered, and 11β-HSD1 levels were increased in postnuclear fractions isolated from PAE mouse hippocampal formation. These neurochemical alterations were associated with reduced context discrimination. CONCLUSIONS: The data support a model in which PAE leads to increased nuclear localization of GRs secondary to reductions in FKBP51 and increases in 11β-HSD1 levels in the adolescent mouse hippocampal formation. Persistent dysregulation of GR subcellular distribution is predicted to damage the hippocampal formation and may underlie many of the effects of PAE on hippocampal-dependent functioning.